ผลของการจัดกิจกรรมการเรียนรู้ภาษาไทยโดยใช้รูปแบบการสอนเบรนทาร์เก็ต ที่มีต่อความสุขในการเรียนและความคงทนในการเรียนรู้ของนักเรียนมัธยมศึกษาปีที่ 1 EFFECTS OF ORGANIZING THAI LANGUAGE LEARNING ACTIVITIES BY USING THE BRAIN-TARGETED TEACHING MODEL ON HAPPINE - คงวิจิตต์, พิณพนธ์; แข็งขัน, พรทิพย์ (An Online Journal of Education, 2014)
การวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาและเปรียบเทียบผลของการจัดกิจกรรมการเรียนรู้ภาษาไทยโดยใช้รูปแบบการสอนเบรนทาร์เก็ตกับการจัดกิจกรรมการเรียนรู้ภาษาไทยแบบปกติที่มีต่อความสุขในการเรียนและความคงทนในการเรียนรู้ของนักเรียนมัธยมศึกษาปีที่ 1 กลุ่มตัวอย่าง คือ นักเรียนมัธยมศึกษาปีที่ 1 ภาคเรียนที่ 2 ปีการศึกษา 2556 โรงเรียนสามเสนวิทยาลัย จำนวน 100 คน แบ่งเป็นกลุ่มทดลองซึ่งจัดกิจกรรมการเรียนรู้โดยใช้รูปแบบการสอน เบรนทาร์เก็ตและกลุ่มควบคุมซึ่งจัดกิจกรรมการเรียนรู้แบบปกติ กลุ่มละ 50 คน เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูล คือ แบบสอบถามความสุขในการเรียนภาษาไทย แบบรายงานความสุขในการเรียนภาษาไทยและแบบสอบผลสัมฤทธิ์การเรียนรู้ภาษาไทยฉบับที่ 1 และ 2 เครื่องมือที่ใช้ในการทดลอง คือ แผนการจัดการเรียนรู้ภาษาไทยโดยใช้รูปแบบการสอนเบรนทาร์เก็ตและแผนการจัดการเรียนรู้ภาษาไทยแบบปกติ ใช้ระยะเวลาทดลอง 8 สัปดาห์ รวม 48 คาบ วิเคราะห์ข้อมูลโดยหาค่ามัชฌิมเลขคณิต ( ) ค่าส่วนเบี่ยงเบนมาตรฐาน (S.D.) และทดสอบค่า t (t-test) ผลการวิจัยสรุปได้ดังนี้ 1) กลุ่มทดลองมีความสุขในการเรียนหลังการทดลองสูงกว่าก่อนการทดลอง อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 2) กลุ่มทดลองมีความสุขในการเรียนหลังการทดลองสูงกว่ากลุ่มควบคุม อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 3) กลุ่มทดลองมีความคงทนในการเรียนรู้สูงกว่ากลุ่มควบคุมอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 The purposes of this research were to study and compare the effects of organizing Thai language learning activities by using the brain-targeted teaching model on happiness learning and learning retention of seventh grade students. The subjects were 100 seventh grade students in semester 2 of academic year 2013 at Samsenwittayalai school in Bangkok. These subjects were divided into two groups: an experimental group learning using the brain-targeted teaching model, and a control group learning by conventional instruction. The instruments for collecting data were the first Thai language learning achievement test, the second Thai language learning achievement test, happiness in Thai language learning questionnaire and happiness in Thai language learning report. The instruments for experiment were lesson plans. The duration of the experiment was 48 periods over a span of eight weeks. The collected data were analyzed by arithmetic means ( ), standard deviation (S.D.) and t-test. The results were as follows: 1) The experimental group had higher happiness in learning after experiment than before stating an experiment at a .05 level of significance. 2) The experimental group had higher happiness learning than the control group at a .05 level of significance. 3) The experimental group had higher learning retention than the control group at a .05 level of significance.